UPAYA UNITED NATION WOMEN DALAM MENINGKATKAN KESETARAAN GENDER DI KENYA - Sari, Erna; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research discusses gender equality problem in kenya during the new kenya konititusi in 2010. explaining effort UN Women in helping government kenya to realize gender equality. That gender equality remains a problem in many areas, both in the social, economic, educational and even governmental fields.This research use the perspective of pluralist, Pluralism is a systematic and framework in which there are several groups or parts of other systems and interconnected with the base of mutual respect and respect among peers. The pluralists view international relationships not only as limited to inter-state relations but also relations between individuals and interest groups where the state is not always the main actor and the sole actor The establishment of UNWOMEN based on the vision of equality contained in the Charter of the United Nations, applies to the elimination of discrimination against women and girls; Women empowerment; and the achievement of equality between women and men as partners and beneficiaries of development, human rights, humanitarian action and peace and security.Keywords: UNWOMEN, gender equality, constitution of kenya 2010